The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1093/nar/28.21.4340
|View full text |Cite
|
Sign up to set email alerts
|

Mutant alleles of Schizosaccharomyces pombe rad9+ alter hydroxyurea resistance, radioresistance and checkpoint control

Abstract: Schizosaccharomyces pombe rad9 mutations can render cells sensitive to hydroxyurea (HU), gamma-rays and UV light and eliminate associated checkpoint controls. In vitro mutagenesis was performed on S.pombe rad9 and altered alleles were transplaced into the genome to ascertain the functional significance of five groups of evolutionarily conserved amino acids. Most targeted regions were changed to alanines, whereas rad9-S3 encodes a protein devoid of 22 amino acids normally present in yeast but absent from mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This method of synchronization has been widely and successfully used to assess the functionality of the G 2 DNA damage checkpoint in wild-type and checkpoint mutants upon ionizing radiation, UVC light and treatment with drugs that produce covalent interstrand cross-links. 39,[41][42][43][44] Cells synchronized in G 2 phase contain 1 single nucleus with 2C DNA content. After exposure to different UVA doses, synchronized cells were released into cell cycle (time 0) whose progression was figure 3A, the appearance of cells with 2 nuclei was delayed by UVA in all tested strains.…”
Section: Resultsmentioning
confidence: 99%
“…This method of synchronization has been widely and successfully used to assess the functionality of the G 2 DNA damage checkpoint in wild-type and checkpoint mutants upon ionizing radiation, UVC light and treatment with drugs that produce covalent interstrand cross-links. 39,[41][42][43][44] Cells synchronized in G 2 phase contain 1 single nucleus with 2C DNA content. After exposure to different UVA doses, synchronized cells were released into cell cycle (time 0) whose progression was figure 3A, the appearance of cells with 2 nuclei was delayed by UVA in all tested strains.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, we found that Egrad9 messenger RNA is expressed in PSc, IGL, and FGL, and established the nuclear location of these transcripts in all cells of protoscoleces. It was demonstrated that cells with altered Rad9 expression are sensitive to DNA damage (Hang et al, 2000; Hopkins et al, 2004; Dang et al, 2005) and defective in aspects of cell cycle checkpoint control (Hirai and Wang, 2002; Hopkins et al, 2004) all along the evolutionary tree. These results suggest that the presence of EgRAD9 in FGL and in PSc of E. granulosus is related to the survival of the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…This was demonstrated by using asynchronously dividing cells, as well as by monitoring populations pulse-labeled with BrdU. Interestingly, S. pombe rad9 null cells are completely unable to delay cycling in G 2 after ionizing radiation exposure (2, 65) but two different point mutants can initiate yet fail to maintain the delays for the same period as in rad9 ϩ cells (31). This raises the possibility that at least one function of Mrad9 in ionizing-radiation-induced G 2 checkpoint control in mammals is to maintain a cycling delay and that other proteins are responsible for the initiation of this checkpoint.…”
Section: Discussionmentioning
confidence: 99%
“…NEO flanked with FRT sites was inserted into the intron. This deletion is predicted to generate a null mutation, based on previous studies with human and fission yeast orthologs indicating the biological significance of this region (31,42,43). Singly targeted cells (see Materials and Methods) were expanded and then treated with a higher concentration of G418 to select for homozygous targeted cells.…”
Section: Methodsmentioning
confidence: 99%